The Cross-Country Incidence of the Global Crisis - Milesi-Ferretti, Gian.; Lane, Philip (Washington, D.C. : International Monetary Fund, 2010)
We examine whether the cross-country incidence and severity of the 2008-2009 global recession is systematically related to pre-crisis macroeconomic and financial factors. We find that the pre-crisis level of development, increases in the ratio of private credit to GDP, current account deficits, and openness to trade are helpful in understanding the intensity of the crisis. International risk sharing did little to shield domestic demand from the country-specific component of output declines, while those countries with large pre-crisis current account deficits saw domestic demand fall by much more than domestic output during the crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet